Spreading and convincing. Radio propaganda during Peronism’s Plan de Emergencia Económica (1952) (Quinto Sol, 2021)
This article studies the production of radio propaganda by the Peronist government during 1952, the time of the presentation and implementation of the Plan de Emergencia Económica. In the midst of an economic crisis and growing political tension scenario, Juan Domingo Perón’s administration presented an economic program that meant a shift in the orientation implemented up to that moment. The government used the production of radio propaganda to disseminate the measures that the Plan de Emergencia Económica implied, and to convince the population to adopt a range of new practices and habits. The actions of the División de Acción Radial, part of the Subsecretaría de Informaciones, are explained, and we analyze two radio productions developed to enhance the impact of the economic Plan presentation. For this purpose, a variety of documentary sources are used, such as radio broadcast audios, scripts, state documentation, newspapers, as well as film and radio magazines. We tackle a key feature for the construction of hegemony of Peronism that was little explored, such as radio, and the relations that the Peronist government established with that media.
Keywords: Peronism; radio; propaganda; hegemony